Az „Alföld szindróma” eredete (vázlat) - Beluszky, Pál (Tér és Társadalom, 1988)
The Alföld has covered a very specific path of social development for centuries. This is reflected in the spatial pattern of its society. E.g. the settlement network in the Alföld has a multitude of so much individual characteristics that one may well speak of a peculiar settlement network only characteristic of the Alföld. Agricultural production in the Alföld was organized within urban frameworks via the so called rural market towns and their scattered farmsteads (the ’tanya’-s); and agriculture has also contributed to urban development. Rural market towns traded the produce of their own vast fields and provided the inhabitants living within their confines with urban goods. It followed from all this that a large proportion of their inhabitants earned living in agriculture; they had hardly any attraction zone or not at all beyond their confines and – apart from the most inner core – they had a village-like appearance. There are scattered farmsteads also in other countries but until recently ’tanya’-s have demonstrated specific features: they represented accessories to the parent settlement, they did not form a settlement on their own: the owner of the farmstead had another home in the rural market town. The rural market town and the ’tanya’-s have been organized into a settlement-management system. There was a specific contradiction between the „economic backwardness" of the Alföld and its social structure the latter being characterized by loose feudal ties until 1848 then by dragging capitalization. Protestantism was the dominant religion in the Alföld with its strong popular ties while in other parts of Hungary the Roman catholic church prevailed. Being aware of these specific features one may well put the question: is it about the simple sum of individual phenomena which occurred in the course of history or a development model, a specific development path which has evolved into a system on its own right. In our opinion it is about the latter and this specific path of development is a mix of three elements: Hungary is situtated within a border-zone between the Western- and the Eastern European models of social development and most historians suggest an individual – Central European – model of development within this border zone. Applying the theory of historical regions to Hungarian spatial development some Hungarian geographers are of the opinion that the inconformity of the Alföld derives from the fact that this region, surrounded by areas displaying „Central European" features of development, followed an Eastern European model of development. In the author’s opinion this assumption is fallacious. Feudalism has never firmly established in the Alföld (pagan, semi-nomadic people settled in here as late as the 13th centrury!) while already at the turn of the 15th-16th centuries the society showed post-feudal features which were, in many aspects, similar to the Western European model: strong local autonomies, no villeins in gross, autonomous churches etc). But this free peasant society did not capitalize. This development path or some of its elements can be related to the Swiss or the Tyrolese societal development. At the same time Alföld represented a periphery within peripheral Hungary itself (e.g. in the 16th-17th centuries, during the Turkish occupation Alföld payed taxes to both the Turks and the Hungarians). Societal development with its Western traits and economic backwardness produced the incongruence of social development with the economic one. Finally, the Alföld remained a ’frontier’ zone during and after the Turkish occupation as well when the reconquest of the lands grown wild kept the frontier features alive. Therefore, the Alföld represented a periphery of the ’frontier’ type lin its „idea) typical form" until the end of the 19th century) which is situated in the border zone between the Western and the Eastern European socio-economic development models and demonstrated certain Western traits (free peasantry) the impacts of which can be revealed up to date.